1998
DOI: 10.1055/s-2007-971904
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Accusport®Lactate Analyser

Abstract: An investigation of the Accusport Lactate Analyser (ACC) was undertaken to assess its accuracy, linearity, reliability, and versatility. Accuracy was determined by comparing 32 blood assays on the ACC with those obtained using the Kodak Ektachem E250 (E250). Linearity was determined over the range 1.2-18.7 mmol/L. Reliability was measured at 1.7 (low) and 14.4 (high) mmol/L concentrations. Versatility involved determining the optimal sample volume, influence of haematocrit, and the effect of time delay from sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 2 publications
2
33
0
3
Order By: Relevance
“…A number of other studies have examined the accuracy of the Accusport lactate analyzer in athletes, 14,15 neonates, 16,17 and critically ill patients. 18,19 Studies that have used BlandAltman analysis showed that mean differences (95% LOA) were similar to our findings, Ϫ0.2 (Ϫ1.2 to 0.8), 16 Ϫ0.3 (Ϫ1.33 to 0.69), 18 and for a study that tested 2 Accusport machines with machine A Ϫ0.4 (Ϫ1.8 to 1.1) and machine B Ϫ0.4 (Ϫ1.5 to 0.7).…”
Section: Discussionmentioning
confidence: 99%
“…A number of other studies have examined the accuracy of the Accusport lactate analyzer in athletes, 14,15 neonates, 16,17 and critically ill patients. 18,19 Studies that have used BlandAltman analysis showed that mean differences (95% LOA) were similar to our findings, Ϫ0.2 (Ϫ1.2 to 0.8), 16 Ϫ0.3 (Ϫ1.33 to 0.69), 18 and for a study that tested 2 Accusport machines with machine A Ϫ0.4 (Ϫ1.8 to 1.1) and machine B Ϫ0.4 (Ϫ1.5 to 0.7).…”
Section: Discussionmentioning
confidence: 99%
“…After a 5-minute warm-up in the same cycle ergometer where the test would be conducted with a 15-Watt (W) load, the individuals pedaled at a constant speed of 28 Km.h -1 with an initial load of 25 W, which was increased by 25 W every three minutes. At the end of each 3-minute stage, the heart rate (HR) was measured with a Polar (S610 I) cardiac monitor and a 50-µL blood sample was collected from the ear lobe in heparinized capillary tubes; while the volunteer started the next exercise stage, the sample's lactate concentration was determined using an Accutrend portable lactate analyzer (Roche) 16 . The duration of this procedure was shorter than 30 seconds.…”
Section: Anaerobic Threshold (Ant) Determinationmentioning
confidence: 99%
“…Foram coletados aproximadamente 25 µL de sangue por capilar do lóbulo da orelha com o uso de lancetas descartáveis marca Feathe. Para as análises foi utilizado lactímetro portátil (Accusport® -Boeringer Mannheim), anteriormente descrito e validado (FELL et al, 1998;INTERDONATO;LUETKEMEIER, 1999). A cinética de remoção do lactato foi realizada em quatro momentos distintos: anteriormente ao aquecimento (medida de repouso-valores Pré), logo após a saída dos competidores do rio (Pós 0'), 5 minutos depois (Pós 5') e 20 minutos após a coleta Pós 0' (Pós 20').…”
Section: Protocolo De Investigaçãounclassified